Pengembangan Sistem Informasi Manajemen Korespondensi berbasis Web dengan Metode Rational Unified Process pada Balai Besar Taman Nasional Bromo Tengger Semeru - Jabbar Satrio Wicaksono; Ismiarta Aknuranda; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Balai Besar Taman Nasional Bromo Tengger Semeru (BBTNBTS) as a Technical Implementation Unit from the Ministry of Environment and Forestry has management plan centered around TNBTS area that aims to lay the operational foundation for the management of natural conservation areas in a systematic, focused and integrated manner. BBTNBTS has a letter management activity to support the implementation of those program plan. Letter management activities are still carried out manually to this date, causing several problems, such as the increased risk of losing data recorded in the agenda book, as well as difficulties in searching for specific mail data, monitoring the status of mail processing, and recapitulation of letters. Based on these problems, the solution that can be applied is to develop a correspondence management information system that can be a means to facilitate staff in managing incoming and outgoing letters at BBTNBTS. The web-based information system is built using the Rational Unified Process (RUP) approach, using the PHP programming language that utilizes the CodeIgniter framework and MySQL database. Validation and compatibility tests are also performed to ascertain that the system is feasible to use.